Santé mentale des jeunes des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : l’état des lieux - Beaton, Ann M.; Benoit, Monique; Mulatris, Paulin; Dupuis, Jérémie B. (/Youth Mental Health in Official Language Minority Communities (OLMCs) in Canada: Situation Analysis Minorités linguistiques et société, 2018)

My health, your health, our health at Bishop's University [infographic] - Bishop's University; Consortium National de formation en Santé; Université de Saint-Boniface (2019)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Suicide mortality gap between Francophones and Anglophones of Quebec, Canada - Burrows, Stephanie; Auger, Nathalie; Tamambang, Lum; Barry, Amadou. D. (Social psychiatry and psychiatric epidemiology, 2013)
Purpose Few studies evaluate language-group differences in suicide mortality. This study assessed the suicide mortality gap between Francophones and Anglophones of Quebec, Canada according to age, sex, method, region and socioeconomic deprivation. Methods Suicide decedents were extracted from the Quebec death file for 1989–2007 (N = 24,465). Age- and sex-specific suicide mortality rates were calculated for four periods (1989–1993, 1994–1998, 1999–2003, 2004–2007) for Francophones and Anglophones aged ≥10 years. Age-standardized rates of suicide by method, region, and level of social and material deprivation were calculated for each sex. Rate ratios and rate differences were estimated. Results Suicide rates for Francophones were two to three times higher than rates for Anglophones, and differences were greatest for adults aged 25–64 years. Francophone males had more than two times the rate of suicide by hanging or firearms than Anglophone males. Francophone females had twice the rate of hanging, poisoning or firearm suicide as Anglophone females, although precision was low. Francophone-Anglophone suicide mortality gaps were higher in urban areas despite lower suicide rates, and varied little across levels of social and material deprivation. Conclusions There was a large suicide mortality gap between Francophones and Anglophones of Quebec; especially, among adults aged 25–64 years.

Availability, accessibility and acceptability of english-language mental health services for the Estrie region’s english-speaking population: Service user and provider perspectives - Charpentier, Claude; Stout, Dale; Benoit, Annie; Poulin, Edith; Philip, Christopher (Journal of Eastern Townships Studies, 2011)
Mental illness affects about 1 in 5 Canadians during their lifetime but only approximately 30% of people needing help actually access mental health ser vices (Gravel, Connolly & Bédard, 2004). This low access rate is worrisome and may not accurately depict the reality as it is lived out by linguistic minorities. The present study documents both the need for and access to English-lan guage mental health services by the Estrie region’s English-speaking minority. Intending to record their needs and access experiences against the backdrop of available English-language mental health services, both users and providers of these services were surveyed in tandem. This novel approach to mental health needs assessment research shows the precarious situation of this minority community (high need/low access to language-congruent mental health ser vices) to be further compromised by misperceptions of service availability.

Ma santé, ta santé, notre santé. Étude sur la santé mentale et les comportements à risque des jeunes adultes dans cinq universités au coeur du Canada - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Consortium national de formation en santé, Université de Saint-Boniface, 2019)
La transition de l’adolescence à la vie adulte constitue une des plus importantes transitions de la vie. À ce stade, le jeune doit développer des habiletés pour être en mesure de se prendre en charge et gérer ses responsabilités académiques et financières tout en maintenant un mode de vie sain. Des études démontrent que des perturbations à ce stade de vie peuvent avoir des conséquences importantes sur la santé psychologique et l’adaptation au changement, et qu’une instabilité émotionnelle peut avoir des retombées sur la performance et le fonctionnement psychosocial. Le milieu universitaire occupe une place privilégiée en tant que lieu d’intervention pour la promotion de la santé pour ces jeunes en raison du contact direct avec les étudiants au cours de plusieurs années. Une stratégie en matière de santé mentale, développée par la Commission de la santé mentale du Canada, souligne que les efforts de promotion en santé mentale et de prévention des troubles mentaux seront plus efficaces si les axes suivants sont respectés 1) savoir à qui s’adresser; 2) renforcer les éléments de protection et réduire les facteurs de risque; 3) fixer des buts clairs; 4) donner aux collectivités ce dont elles ont besoin pour agir; et 5) planifier pour le long terme. Ce projet de recherche s’inspire de cette stratégie : notre but à long terme est de favoriser le bien-être des jeunes adultes qui fréquentent un établissement universitaire en développant un outil de dépistage et des initiatives d’appui soutenables sur le campus et dans la communauté, selon les ressources disponibles. Pour ce faire, nous devons d’abord prendre connaissance de l’état de santé mentale de la population étudiante et des facteurs de risques et de protection qui leur sont propres. Ainsi, les efforts de prévention seront plus efficaces puisqu’ils seront conçus en fonction des besoins de la population cible et en consultation avec cette dernière. Cette étude a été menée dans cinq universités dans trois provinces, soit le Manitoba, l’Ontario et le Québec, dans le but de mieux comprendre l’effet du contexte linguistique sur la santé mentale et les comportements à risque des jeunes universitaires. Les cinq établissements choisis sont principalement des petites universités en contexte linguistique majoritaire (Brandon University et Université du Québec en Abitibi-Témiscamingue) ou minoritaire (Université de Saint-Boniface et Université Bishop’s). De plus, des participants de l’unique université bilingue du pays (Université d’Ottawa) ont participé. Ainsi, nous serons en mesure d’analyser les données en fonction de divers facteurs déterminants, dont le milieu linguistique dans lequel évolue l’étudiant. L’objectif principal de l’étude est de prendre connaissance de l’état de santé mentale et des comportements à risque prédominants des jeunes universitaires en contextes linguistiques majoritaires et minoritaires au Canada et d’identifier les facteurs de protection et de risque associés à leur bien-être. Notre but ultime est d’appuyer les étudiants, particulièrement ceux dans le besoin, dans leur atteinte d’une réussite académique. Ce rapport est descriptif : il présente les données générales se rapportant aux profils sociodémographique et ethnolinguistique, à l’état de santé mentale et aux comportements associés à cet état, ainsi qu’à la sécurité routière, au taxage et au harcèlement sexuel, aux pratiques sexuelles, à la consommation d’alcool, de drogues et de tabac, et à l’usage des nouvelles technologies; le tout, selon le genre et pour chacun des établissements d’enseignement postsecondaire. Un sondage a été distribué, sur papier ou en ligne, en fin novembre 2018 et en février 2019; au total, 2075 étudiants ont participé. Des analyses statistiques de fréquences et de proportions, selon le genre, ont été utilisées pour décrire les participants et leurs comportements.

My Health, your health, our health. A study on mental health and risk-taking behaviors of young adults on five university campuses in the heart of Canada - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Consortium national de formation en santé, Université de Saint-Boniface, 2019)
The transition from adolescence to adulthood is a time of dramatic change in one’s life. At this stage, youth are developing skills to be able to support themselves and manage academic and financial responsibilities, while maintaining a healthy lifestyle. Studies have shown that disturbances at this stage may have a strong impact on one’s psychological health and ability to adapt to change; emotional instability may have repercussions on performance and psychosocial functioning. Due to direct contact with young adults, postsecondary institutions are priviledged settings for health promotion activities. A mental health strategy developed by the Mental Health Commission of Canada suggests that to successfully promote health, and treat and prevent mental health issues, the following should be considered: 1) know who to reach; 2) strengthen protective factors and reduce risk factors; 3) set clear goals; 4) give communities what they need to take action; and 5) plan for the long term. This research project builds on this strategy. Our long term goal is to promote the well-being of university students by developing a screening tool and developing sustainable initiatives on campus and within the community, taking into consideration available resources. As such, we must first gain insight into the mental health status of the student population, including the risk and protective factors specific to these students. Thus, health promotion efforts will be more efficient, as they will have been created according to student needs and in consultation with this population. This study was conducted in five universities in three provinces, Manitoba, Ontario and Quebec, to gain insight into the impact of the linguistic context on mental health and risk-taking behaviors of students. The five participating universities were chosen mainly because of their small size and linguistic environment: Brandon University and the Université du Québec en Abitibi-Témiscamingue are in linguistic majority settings, whereas the Université de Saint-Boniface and Bishop’s University are in linguistic minority communities. In addition, participants were recruited from the only bilingual university in the country (University of Ottawa). Thus, data will be analysed according to various influencing factors, including the linguistic environment. The main objective of this study is to gain insight into the mental health status and predominant risk behaviors of university students in both majority and minority linguistic settings in Canada and to identify protective and risk factors relative to their well-being. The ultimate goal is to help those in need achieve academic success. This report is descriptive: it presents general data related to sociodemographic and ethnolinguistic profiles, mental health and related behaviors, road safety, bullying and sexual harassment, sexual practices, alcohol, drug and tobacco use and use of new technologies, according to gender, for each of the postsecondary institutions. A survey was conducted online or in print form at the end of November 2018 and in February 2019. In total, 2075 students participated. Statistical analysis of frequencies and proportions according to gender were used to describe participants and their behaviors

Do you speak English? Traitement sociopolitique de l’accessibilité aux services en santé mentale pour les anglophones du Québec - Kirouac, Laurie; Perreault, Isabelle (Minorités linguistiques et société, 2018)
À la fin des années 1970, le Québec se dote de la Charte de la langue française (Loi 101), qui modifie l’encadrement de la question de la langue de prestation des services de santé et de services sociaux. Parallèlement, de nombreux rapports, comités d’étude et politiques modifient en profondeur les pratiques institutionnelles et communautaires à l’endroit des personnes aux prises avec des problèmes de santé mentale. Depuis ce contexte de grandes transformations, où certaines réponses politiques ont été apportées aux préoccupations linguistiques, qu’en est-il de l’accès aux soins de santé mentale pour les anglophones du Québec ? Nous proposons de retracer dans ses grandes lignes l’évolution du traitement sociopolitique qui a été fait de la question de l’accessibilité des services en santé mentale pour les personnes anglophones en accordant une attention particulière à la situation montréalaise. Mots-clés : Québec, anglophones, santé mentale, minorité linguistique, services de santé

Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? - Puchala, Chassidy; Leis, Anne; Lim, Hyun; Tempier, Raymond (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)

Access to health and social services for Quebec’s English-Speaking Minority Communities: Recent challenges, legislative context, and research recommendations. - Shoumarova, Lina (Quebec English-Speaking Communities Research Network, 2024)

Regards croisés Ontario-Québec : les services de soins de santé mentale des communautés de langue officielle en situation minoritaire de 1950 à nos jours - Thifault, Marie-Claude; Lebel, Marie; Perreault, Isabelle; Desmeules, Martin (Reflets, 2012)
Considérant qu’un Canadien sur neuf hospitalisé pour maladie mentale retournera à l’urgence moins d’un mois après sa sortie d’hôpital, il importe de documenter, dans une perspective socio-historique, les itinéraires « transinstitutionnels » des personnes souffrant de troubles psychiques. Nous proposons ici une note de recherche sur l’enquête que nous menons sur l’évolution des services de soins de santé mentale des communautés de langue officielle en situation minoritaire, en particulier, les communautés francophones de l’Est et du Nord ontarien ainsi que de la communauté anglophone de l’Ouest du Québec. Ces regards croisés entre deux régions francophones de l’Ontario et le Montréal anglophone visent une meilleure compréhension de l’impact des facteurs de « langue de service » et de « culture » sur la santé mentale des communautés francophones en situation minoritaire (CFSM). Mots-clés : services de santé mentale, désinstitutionnalisation, minorités linguistiques, Ontario, Québec

Comparing the rates of mental disorders among different linguistic groups in a representative Canadian population - Vasiliadis, Helen-Maria; Lepnurm, Marje; Tempier, Raymond; Kovess-Masfety, Viviane (Social psychiatry and psychiatric epidemiology, 2012)
Purpose We aimed to determine whether linguistic group influences reported prevalence rates for a number of common mental disorders. Methods Secondary data analyses of the Canadian Community Health Survey cycle 1.2 (CCHS 1.2) were carried out on representative bilingual French and English, monolingual French and English and other language groups in Canada. Past year prevalence of major depression, anxiety disorders (agoraphobia, social phobia, panic disorder) and alcohol abuse/dependence were ascertained using versions of the World Mental Health Composite International Diagnostic Interview (WMH-CIDI) questionnaire. Multivariate data analyses were used to model past year presence of a mental disorder as a function of linguistic group, defined as languages can converse in, and adjusting for socioeconomic, demographic and cultural factors. Results Overall, past year rates for the presence of a common mental disorder were 10.7% (9.7–11.7%) for the bilingual English; 9.0% (8.1–9.9%) for the bilingual French; 10.2% (9.8–10.6) for the monolingual English; 8.5% (7.7–9.3%) for the monolingual French; and 8.3% (6.1–10.4%) for the other language group. After adjusting for a number of socio-demographic, economic and cultural factors, the multivariate analyses showed that the linguistic groups were equally likely to report the presence of a past year common mental disorder. This was also true for comparisons between the bilingual participants responding in French and English. Conclusions The differences observed in the reported crude rates for the presence of mental disorders across the different linguistic groups in Canada were explained by socio-demographic, economic, and factors such as immigration, spoke a third language and province of residence, and not explained by language of interview.